Patient experiences of being cared for by nursing students in a psychiatric education unit. (September 2020) - Andersson, Niklas; Ekebergh, Margaretha; Hörberg, Ulrica
Patients are vital for student learning. However, research has primarily focused on student nurse learning from a student or supervisor perspective; few studies have investigated patient perspectives. This study examines student care practice for patients in acute psychiatric day care. The aim was to describe patients' experiences of care by student nurses in a psychiatric education unit, a collaboration between the clinic and academia. Data were collected through 17 lifeworld interviews with patients, of which 10 also included observations. Data have been analysed for meanings using reflective, lifeworld research (RLR). The findings reveal that the encounters involve an interactive process of giving and receiving, providing students with both health opportunities and risks. The findings can further be described by the following constituents: exposed and vulnerable ; responsibility to support ; the importance of accessibility ; reciprocity ; and engagement that evokes the desire to live a life with dignity . In a patient–student community, there are prerequisites for proper caring. Patient health seems to be positively affected when patients are involved in both their own care and student learning.